Making History in Twentieth-Century Quebec - Rudin, Ronald (Book collections on Project MUSE., 1997)
"This book is the first comprehensive examination of the way in which French-speaking Quebecers have written about their past in the twentieth century. Rudin begins his study with Lionel Groulx, a professional historian who dominated the field for the first half of the century, and concludes with figures such as Paul-Andre Linteau who occupy an important place in the discipline today." "As a complementary volume to Carl Berger's The Writing of Canadian History, and as a new, critical reading of Quebec historiography, this book will stimulate considerable debate in the historical community."--Jacket